Effects of continuous high-dose G-CSF administration on hematopoietic stem cell mobilization and telomere length in patients with amyotrophic lateral sclerosis – a pilot study. (August 2019) - Iberl, Sabine; Meyer, Anne-Louise; Müller, Gunnar; Peters, Sebastian; Johannesen, Siw; Kobor, Ines; Beier, Fabian; Brümmendorf, Tim H.; Hart, Christina; Schelker, Roland; Herr, Wolfgang; Bogdahn, Ulrich; et al.
Highlights: We monitored six ALS patients up to 3.5 years. Continuous high-dose G-CSF administration was safe. Despite intense G-CSF treatment mobilization of CD34 + HSPC was not enhanced. Long-term G-CSF application did not shorten telomeres in ALS patients' leukocytes. Serum cytokines revealed G-CSF-mediated immunomodulatory and proteolytic effects. Abstract: Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease of complex and still poorly understood etiology. Loss of upper and lower motoneurons results in death within few years after diagnosis. Recent studies have proposed neuroprotective and disease-slowing effects of granulocyte-colony stimulating factor (G-CSF) treatment in ALS mouse models as well as humans. In this study, six ALS patients were monitored up to 3.5 years during continuous high-dose G-CSF administration. Repetitive analyses were performed including blood count parameters, CD34 + hematopoietic stem and progenitor cell (HSPC) and colony forming cell (CFC) counts, serum cytokine levels and leukocyte telomere length. We demonstrate that continuous G-CSF therapy was well tolerated and safe resulting in only mild adverse events during the observation period. However, no mobilization of CD34 + HSPC was detected as compared to baseline values. CFC mobilization was equally low and even a decrease of myeloid precursors was observed in some patients. Assessment of telomere length within ALS patients' leukocytes revealed that G-CSF did not significantly shorten telomeres, while those of ALS patients were shorter compared to age-matched healthy controls, irrespective of G-CSF treatment. During G-CSF stimulation, TNF-alpha, CRP, IL-16, sVCAM-1, sICAM-1, Tie-2 and VEGF were significantly increased in serum whereas MCP-1 levels decreased. In conclusion, our data show that continuous G-CSF treatment fails to increase circulating CD34 + HSPC in ALS patients. Cytokine profiles revealed G-CSF-mediated immunomodulatory and proteolytic effects. Interestingly, despite intense G-CSF stimulation, telomere length was not significantly shortened.